Hubungan Tipe Kepribadian dengan Academic Burnout pada Mahasiswa Keperawatan di Kota Bandung - Nabilah Nurfaidah; Kusdiyati, Sulisworo (Bandung Conference Series: Psychology Science, 2024)
Abstract. Academic burnout is a condition where an individual feels emotional confusion, then there is a feeling and behavior of distancing themselves from academic tasks and also a feeling of lack of confidence in their abilities as a student. There are factors that contribute to academic burnout, one of which is personality. Personality is a distinctive characteristic of an individual that can differentiate one individual from another. This research aims to see the relationship between personality type and academic burnout. This research uses a quantitative approach with a correlational research design. The measuring instrument used to measure academic burnout is the Maslach Inventory-Student Survey (MBI-SS) compiled by Schaufeli et al (2002) and adapted by Fitri Arlinkasari and Sari Zakiah (2017) and to measure personality types the Big Five Inventory measuring instrument is used. (BFI) 28-item version which has been adapted by Neila Ramadhani (2012). The data analysis technique used is the Spearman's Rank correlation test with the results of the personality types extraversion, conscientiousness, neuroticsm having a relationship with academic burnout as seen from the significant value greater than 0.05. Abstrak. Academic burnout adalah kondisi individu yang merasakan kelalaham emosional, lalu adanya perasaan juga perilaku menjauh dari tugas akademik dan juga adanya rasa tidak percaya diri akan kemampuan dirinya sebagai mahasiswa. Terdapat faktor yang berkontribusi pada academic burnout, salah satunya adalah kepribadian. Kepribadian merupakan karaktersitik khas dari seorang individu yang dapat membedakan individu satu dengan individu lainnya. Penelitian ini bertujuan untuk melihat bagaimana hubungan antara tipe kepribadian dengan academic burnout. Penelitian ini menggunakan pendekatan kuantitatif dengan desain penelitian korelasional. Alat ukur yang digunakkan untuk mengukur academic burnout adalah Maslach Inventory-Student Survey (MBI-SS) yang disusun oleh Schaufeli et al (2002) dan diadaptasi oleh Fitri Arlinkasari dan Sari Zakiah (2017) dan untuk mengukur tipe kepribadian digunakan alat ukur Big Five Inventory (BFI) versi 28-item yang sudah diadptasi oleh Neila Ramadhani (2012). Teknik analisis data yang digunakkan adalah uji korelasi Rank Spearman’s dengan hasil tipe kepribadian extraversion, conscientiousness, neuroticsm memiliki hubungan dengan academic burnout terlihat dari nilai signifikan lebih besar dari 0.05.